Feasibility of Hydrogen Energy in Multi End-use Setting in Buildings - Saleh, Rana Khaled Mohammed Mohammed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
In the present study, an investigation is conducted to assess the feasibility of producing hydrogen from water and storing it to be used later for electricity generation in a fuel cell. For this reason, it is assumed that a group of hotels that already own a reverse osmosis (RO) desalination unit and an installed 5-MW photovoltaic (PV) system, form a cooperative and share the usage of the hydrogen system. The sales of the byproduct oxygen is also of consideration in the viability study. Hydrogen is generated throughout the year under two scenarios; In the winter period where off-peak electricity is used, and in the remaining seasons where daytime photovoltaic electricity in the grid is used for water splitting by electrolysis to obtain hydrogen. In both scenarios hydrogen is stored during off-peak hours and electricity is generated in a fuel cell during peak hours in North Cyprus. Through the economic analysis, it has been noticed that the system is non-feasible under the current tariff billing. However, using optimization methods through sensitivity analysis and applying Monte Carlo simulation, together with proposing a multi-tariff billing system, it has been observed that the system can become feasible. Through optimization, the fuel cell energetic and exergetic efficiencies are increased to 50.19% and 48.09%, respectively. It is found that the break-even peak and off-peak tariff prices should be 0.55 and 0.275 $/kWh, respectively, with expected reduction in fuel cell and storage unit costs in the future, to obtain savings-to-investment ratios above unity. The analysis was done over a lifetime of 15 years and discount rate of 2%.

ÖZ: Bu çalışmada, sudan hidrojen üretip depolamak suretiyle bir yakıt hücresi vasıtasıyla elektrik üretiminin fizibilitesini değerlendirmek için bir araştırma yapılmıştır. Bu nedenle, denize yakın bir otel gurubunun halihazırda bir ters ozmoz (RO) suyu tuzdan arındırma ünitesine ve kurulu 5 MW'lık bir fotovoltaik (PV) sistemine sahip olduğu, bir kooperatif oluşturduğu ve hidrojen sisteminin kullanımını paylaştığı varsayılmaktadır. Yan ürün oksijenin satışı da fizibilite çalışmasında dikkate alınmıştır. Hidrojen yıl boyunca iki senaryo altında üretilir; Kış döneminde elektriğin yoğun kullanılmadığı saatlerde ve diğer mevsimlerde, fotovoltaiklerin elektrik ürettiği gündüz saatlerinde elektroliz yoluyla arıtılmış suyu bölerek elde edilir. Her iki senaryoda da Kuzey Kıbrıs'ta yoğun olmayan saatlerde hidrojen depolanır ve yoğun saatlerde bir yakıt hücresinde elektrik üretilir. Sistemin mevcut tarife ile uygulanabilir olmadığı yapılan ekonomik analizde ortaya çıkmıştır. Ancak duyarlılık analizi ile optimizasyon yöntemlerinin kullanılması ve Monte Carlo simülasyonunun uygulanması, çok tarifeli faturalandırma sisteminin önerilmesiyle birlikte sistemin uygulanabilir hale gelebileceği gözlemlenmiştir. Optimizasyon sayesinde, yakıt hücresi enerjik ve ekserjetik verimlilikleri sırasıyla %50.19 ve %48.09'a yükseltildi. Fizibilitede başabaş gitmek için, gelecekte beklenen yakıt hücresi ve depolama fiyatlarının düşmesi yanında, yoğun ve yoğun olmayan saatlerdeki elektrik fiyatının sırasıyla 0.8 ve 0.4 $/kWh olması gerektiği bulunmuştur. Analiz, 15 yıllık bir ömür ve %2 iskonto oranı üzerinden yapılmıştır.
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2022. Supervisor: Prof. Dr. Uğur Atikol.
Keywords: Mechanical Engineering; Hydrogen Energy--Storage--Buildings; Hydrogen as fuel; Renewable energy sources; Energy storage, hydrogen energy, economic feasibility, demand curve, sensitivity analysis, Monte Carlo